THE MASCULINITY AND FEMININITY TRAITS OF FEMALE CHARACTER IN ROTH’S INSURGENT NOVEL - Fatimah, Siti; Sili, Surya; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
Woman and man are often seen as two individuals with different characteristics. Women are labeled with feminine characteristics and men are labeled with masculine characteristics. Women often considered have lower status than men by not having the characteristics of men. However, the existence of masculinity traits in a female character is still possible to happen considering masculinity and femininity are concept created by society. By this research, the researcher aimed to analyze the masculinity and femininity traits of female character in Roth’s Insurgent Novel. This research has two purposes. The first is to analyze the masculine traits of Beatrice Prior, and the second is to analyze the feminine traits of Beatrice Prior. The researcher applied Sandra L Bem theory to answer the research questions. This research is under qualitative paradigm. Content analysis was applied in this research. The findings of this research showed that Beatrice Prior has eighteen masculine traits and five feminine traits. By the result of this research, it can be concluded that female individual can have more masculine traits or vise versa which then gives more understanding to the researcher. In addition, this research strengthens the idea that novel can be used as a tool to raise the awareness of the readers about th phenomena that happen in the society. Wanita dan pria seringkali dipandang sebagai dua individu dengan karakteristik berbeda. Wanita dilabeli dengan karakteristik feminin dan pria dilabeli dengan karakteristik maskulin. Wanita sering dianggap memiliki status lebih rendah daripada pria dengan tidak memiliki karakteristik pria. Namun, keberadaan ciri-ciri maskulinitas dalam karakter perempuan masih mungkin terjadi mengingat maskulinitas dan feminitas adalah konsep yang diciptakan oleh masyarakat. Dengan penelitian ini, peneliti bertujuan untuk menganalisis sifat-sifat maskulinitas dan femininitas karakter perempuan dalam Roth's Insurgent Novel. Penelitian ini memiliki dua tujuan. Yang pertama adalah untuk menganalisis sifat-sifat maskulin dari Beatrice Prior, dan yang kedua adalah untuk menganalisis sifat-sifat feminin dari Beatrice Prior. Peneliti menerapkan teori Sandra L Bem untuk menjawab pertanyaan penelitian. Penelitian ini adalah penelitian kualitatif. Penelitian ini berkaitan dengan teknik analisis konten. Temuan penelitian ini menunjukkan bahwa Beatrice Prior memiliki delapan belas ciri maskulin dan lima ciri feminin. Dari hasil penelitian ini, dapat disimpulkan bahwa individu perempuan dapat memiliki lebih banyak sifat maskulin atau sebaliknya yang kemudian memberikan lebih banyak pemahaman kepada peneliti. Selain itu, penelitian ini memperkuat gagasan bahwa novel dapat digunakan sebagai alat untuk meningkatkan kesadaran pembaca tentang fenomena yang terjadi di masyarakat.